Cycling in triathlon: Is it really as simple as riding a bike? - Burr, J. F.; Warburton, D. E. R. (Strength and Conditioning Journal, 2011)
The cycling leg of a triathlon imposes unique physiological and biomechanical demands on athletes compared with cycle racing. By recognizing these differences, athletes and coaches can use training practices to optimize adaptations according to the principle of specificity. The primary emphasis is on aerodynamic form and efficiency training.